Expressive Speech Acts of The Main Character in Tim Burton's Corpse Bride: A Pragmatic Analysis - Tiara Ananda Arifah; Qanitah Masykuroh (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to classify the types and intentions of expressive speech acts of the main character, Victor Van Dort, in Tim Burton's 2005 Corpse Bride Movie. Methodology: Utilizing a qualitative approach, this text analysis investigates Victor Van Dort's utterances containing expressive speech acts. The data were collected from the movie script using document analysis. The data were analysed deploying the framework of speech act theory by Searle (1979) and contextual pragmatics based on Holmes (2001) to understand the situational and social contexts that influence speech and its meaning.Results: The analysis found 33 expressive speech acts i.e. eight apologizing, seven agreements, five attitudes, five exclamations, three wishes, two thanking, two lamentation, and one greeting. These speech acts mainly describe psychological conditions and emotional reactions. It is important to note the absence of speech acts such as congratulations or condolances, which indicates that the focus of the narrative is on personal emotional experiences rather than social rituals. The meaning of each expressive speech act has also been identified.Applications/Originality/Value: This study highlights the importance of how expressive speech acts contribute to deepening emotions and character development to strengthen the movie's narratives.